Diurnal time-activity budgets and habitat use of Lesser Snow Geese Anser caerulescens in the middle Missouri River valley during winter and spring - Davis, Susan E; Klaas, Erwin E; Koehler, Kenneth J (Wildfowl, 1989)
Diurnal time activity and habitat use of wintering and spring-migrating Lesser Snow Geese were studied in the middle Missouri River valley during 1983 and 1984. Geese spent the majority of daylight hours sleeping and loafing. During winter and spring migration, geese spent 17.5% and 24.0% of a 12-h day feeding, respectively. Geese primarily fed in corn stubble fields; they also fed on winter wheat and bromegrass. The availability of waste corn in the middle Missouri River valley presumably influences the winter distribution of Snow Geese.